HW01 solution - mao (tm23477) – HW01 – Radin –...

Info iconThis preview shows pages 1–3. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: mao (tm23477) – HW01 – Radin – (56570) 1 This print-out should have 22 questions. Multiple-choice questions may continue on the next column or page – find all choices before answering. 001 10.0 points Determine if lim x → 4 √ x + 5 − 3 x − 4 exists, and if it does, find its value. 1. limit = 1 6 correct 2. limit = 1 3 3. limit = 5 4. limit = 6 5. limit = 1 7 6. limit does not exist Explanation: Since ( √ x + 5 − 3)( √ x + 5 + 3) = ( x + 5) − 9 = x − 4 , we see by rationalizing the numerator that √ x + 5 − 3 x − 4 = x − 4 ( x − 4)( √ x + 5 + 3) = 1 √ x + 5 + 3 provided x negationslash = 4. On the other hand, lim x → 4 √ x + 5 + 3 = 6 . Consequently, by properties of limits, lim x → 4 √ x + 5 − 3 x − 4 exists and has limit = 1 6 . 002 10.0 points Find the value of lim x →− 4 7 x + 4 parenleftbigg 4 x 2 + 8 − 1 6 parenrightbigg . 1. limit does not exist 2. limit = 7 12 3. limit = 7 36 4. limit = 7 24 5. limit = 7 18 correct Explanation: After the second term in the product is brought to a common denominator it becomes 24 − x 2 − 8 6( x 2 + 8) = 16 − x 2 6( x 2 + 8) . Thus the given expression can be written as 7(16 − x 2 ) 6( x + 4)( x 2 + 8) = 7(4 − x ) 6( x 2 + 8) so long as x negationslash = − 4. Consequently, lim x →− 4 7 x + 4 parenleftbigg 4 x 2 + 8 − 1 6 parenrightbigg = lim x →− 4 7(4 − x ) 6( x 2 + 8) . By properties of limits, therefore, limit = 7 18 . 003 10.0 points mao (tm23477) – HW01 – Radin – (56570) 2 Find the derivative of f when f ( x ) = 1 − 2 cos x sin x . 1. f ′ ( x ) = 1 − 2 cos x sin 2 x 2. f ′ ( x ) = 2 sin x + 1 cos 2 x 3. f ′ ( x ) = 2 + sin x cos 2 x 4. f ′ ( x ) = 2 − cos x sin 2 x correct 5. f ′ ( x ) = − 2 + cos x sin 2 x 6. f ′ ( x ) = − 1 + 2 cos x sin 2 x 7. f ′ ( x ) = 2 sin x − 1 cos 2 x 8. f ′ ( x ) = sin x − 2 cos 2 x Explanation: By the quotient rule, f ′ ( x ) = 2 sin 2 x − cos x (1 − 2 cos x ) sin 2 x = 2(sin 2 x + cos 2 x ) − cos x sin 2 x . But cos 2 x + sin 2 x = 1. Consequently, f ′ ( x ) = 2 − cos x sin 2 x . 004 10.0 points Find the derivative of f when f ( x ) = 4 x cos 3 x − 2 sin 3 x . 1. f ′ ( x ) = 6 cos 3 x − 2 x sin 3 x 2. f ′ ( x ) = − 12 x sin3 x − 2 cos 3 x correct 3. f ′ ( x ) = 12 x sin 3 x − 2 cos 3 x 4. f ′ ( x ) = − 12 x sin3 x − 6 cos3 x 5. f ′ ( x ) = − 6 cos 3 x + 12 x sin3 x Explanation: Using formulas for the derivatives of sine and cosine together with the Product and Chain Rules, we see that f ′ ( x ) = 4 cos3 x − 12 x sin 3 x − 6 cos3 x = − 12 x sin 3 x − 2 cos 3 x ....
View Full Document

This note was uploaded on 05/12/2010 for the course M 408L taught by Professor Radin during the Spring '08 term at University of Texas.

Page1 / 9

HW01 solution - mao (tm23477) – HW01 – Radin –...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online